A systematic review and meta-synthesis of policy intervention characteristics that influence the implementation of government-directed policy in the hospital setting: implications for infection prevention and control. Issue 3 (May 2020) - Havers, Sally M; Kate Martin, Elizabeth; Wilson, Andrew; Hall, Lisa
Background: Government-directed policy plays an important role in the regulation and supervision of healthcare quality. Effective implementation of these policies has the potential to significantly improve clinical practice and patient outcomes, including the prevention of healthcare-associated infections. A systematic review of research describing the implementation of government-directed policy in the hospital setting was performed with the aim to identify policy intervention characteristics that influence implementation. Methods: A systematic search of four electronic databases was undertaken to identify eligible articles published between 2007 and 2017. Studies were included if published in the English language and described the implementation of government-directed policy in a high-income country hospital setting. Data on policy and implementation were extracted for each article and interpretive syntheses performed. Results: A total of 925 articles were retrieved and titles and abstracts reviewed, with 69 articles included after review of abstract and full text. Qualitative synthesis of implementation data showed three overarching themes related to intervention characteristics associated with implementation: clarity; infrastructure; and alignment. Conclusion: Better understanding and consideration of policy intervention characteristics during development and planning will facilitate more effective implementation although research describing implementation of government-directed policy in the hospital setting is limited and of variable quality. The findings of this study provide guidance to staff tasked with the development or implementation of government-directed policy in the hospital setting, infection prevention and control professionals seeking to maximise the impact of policy on practice and improve patient outcomes.